Estimation of Indoor 222Rn Concentration in Lima, Peru Using LR-115 Nuclear Track Detectors Exposed in Different Modes - Pereyra Anaya, Patrizia Edel (2023)
Radon is the main source of natural radioactivity, and its measurement is considered extremely important in radioprotection, given its relationship with the occurrence of lung cancer. In the last two years, measurements of this radioactive gas were carried out in Lima considering a grid of 5 km (Formula presented.) and the population density to determine the number of measurements to be carried out. Cellulose nitrate nuclear track detectors exposed in bare mode and diffusion chamber mode were used to estimate (Formula presented.) Rn concentrations. In diffusion chamber mode, non-commercial monitors and commercial monitors were used. The monitoring results are presented for 43 districts of the Lima Province whose population is approximately ten million inhabitants occupying a total area of 2655.15 km (Formula presented.). Measurements were made obtaining an average concentration of 49 Bq·m (Formula presented.) using bare detectors and 66 Bq·m (Formula presented.) using non-commercial diffusion chambers. Average concentrations obtained by both detector exposure modes were below the maximum concentration recommended by the WHO. A radon ((Formula presented.) Rn) map was also obtained as a visual representation of the (Formula presented.) Rn levels in the Lima province using inverse distance weighting (IDW) interpolation.